Worldviews : an introduction to the history and philosophy of science - DeWitt, Richard (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2010)
"Updated throughout and with three entirely new chapters, Worldviews: An Introduction to the History and Philosophy of Science, Second Edition furthers its reputation as the definitive introductory text on the historical developments and philosophical issues that inform our scientific view of the world around us. Represents an innovative introduction to the history and philosophy of science, designed especially for those coming to the subject for the first time. Updated new edition features the addition of chapters focusing on scientific laws, evolutionary theory, and implications of evolution. Covers the key historical developments and philosophical themes that have impacted our scientific view of the world around us. Analyzes the transitions from the Aristotelian worldview to the Newtonian worldview to a new and currently developing worldview. Explores challenges to the Western scientific worldview brought on by recent discoveries"--
"Worldviews: An Introduction to the History and Philosophy of Science is an ideal text for those coming to the history and philosophy of science for the first time. This volume introduces fundamental conceptual issues, explores the transition from the Aristotelian worldview to the Newtonian worldview, and considers challenges to our own western worldview brought on by developments in twentieth-century science, most notably relativity theory and quantum theory. Covering the key historical developments and philosophical themes and topics that have had the deepest impact on our scientific view of the world around us, this accessible and engaging book is perfect for anyone newly interested in the nature and development of western scientific thought"--
Part I: Fundamental issues. -- Part II: The transition from the Aristotelian worldview to the Newtonian worldview. -- Part III: Recent developments in science and worldviews.
Includes bibliographical references (p. [366]-370) and index.
Keywords: Science -- History; Science -- Philosophy